Jindal journal of business research. - O. P. Jindal Global University ([New Delhi] : Sage Publications, 2012)
JJBR is a reflection of rapidly developing management research in emerging market economies (EMEs), particularly of Asia and their increasing global economic impact. JJBR aims to address the fundamental problems of business management in a multidisciplinary framework.
Volume 1, number 1 (June 2012); title from cover image (viewed January 26, 2014).
Volume 9, number 1 (June 2020) (SAGE Journals, viewed July 10, 2020).
Keywords: Business -- Periodicals; Industrial management -- India -- Periodicals; Industrial management -- Asia -- Periodicals; Industrial management; Business; Business -- Research; India; Asia; Management studies, Business Administration, Organizational Science (General); Management, bedrijfskunde, organisatiekunde (algemeen); Electronic journals; Periodicals